Negative temperature coefficient thermistor material with double perovskite structure and preparation method of negative temperature coefficient thermistor material
By adopting the thermistor material with a dual perovskite structure, the problems of unstable phase structure and resistivity drift in traditional NTC thermistors at high temperatures are solved, and the high-temperature negative temperature coefficient characteristics with stable electrical performance in the temperature range of 400℃-1200℃ are achieved.
Patent Information
- Application Number
- CN202411819223.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-28
AI Technical Summary
The traditional spinel NTC thermistor has an unstable phase structure under high temperature environments and cannot be used for a long time at temperatures of 800°C or above, and the resistivity drifts severely.
The negative temperature coefficient thermistor material with a double perovskite structure is prepared by barium carbonate, calcium carbonate or strontium carbonate, dilanthanum trioxide, neodymium trioxide or samarium trioxide and niobium pentoxide as raw materials, and is prepared by ball milling, drying, grinding, calcining, re-ball milling, drying, grinding, cold isostatic molding and high-temperature sintering to obtain the thermistor material with obvious negative temperature coefficient characteristics.
In the temperature range of 400°C-1200°C, the material exhibits typical NTC characteristics, stable electrical properties and good aging performance, and is suitable for use in the thermistors in high temperature environments.
Smart Images

Figure CN119707489A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of semiconductor sensors, and in particular relates to a double perovskite structure negative temperature coefficient thermistor material and a preparation method thereof. Background Art
[0002] With the booming development of deep-sea exploration, military and aerospace, and automotive electronics industries, the demand for sensitive components for sensing, monitoring, and control systems with high precision and the ability to withstand harsh environments is growing, and materials are increasingly being used in extreme environments. As one of the thermal components, NTC (negative temperature coefficient) thermistors have the characteristic that resistance decreases exponentially as temperature increases. NTC thermistors have great development potential in the manufacture of temperature sensors, temperature compensation, voltage stabilization, ultra-high frequency detection equipment, metal thermocouples, and surge current suppression. However, the applicable temperature range of traditional spinel NTC thermistors is -60°C to 300°C, and the phase structure is extremely unstable at high temperatures. Long-term use at temperatures exceeding 300°C will result in significant aging, making it impossible to achieve accurate measurement. When traditional single perovskite-structured thermistor materials are used for a long time in high-temperature environments of 800°C and above, the phase structure will change due to element volatilization and grain boundary side reactions, and the resistivity drifts seriously, and the high-temperature phase stability still needs to be improved. Summary of the invention
[0003] The purpose of the present invention is to provide a double perovskite structure negative temperature coefficient thermistor material and a preparation method thereof, wherein the thermistor material is made of barium carbonate, calcium carbonate or strontium carbonate, lanthanum trioxide, neodymium trioxide or samarium trioxide and niobium pentoxide as raw materials, and is subjected to ball milling, drying, grinding, calcining, re-ball milling, drying, grinding, cold isostatic pressing, and high-temperature sintering to obtain a double perovskite structure material. The double perovskite structure negative temperature coefficient thermistor material of the present invention has obvious negative temperature coefficient characteristics in the temperature range of 400°C-1200°C, stable electrical properties, and stable aging properties, and is a thermistor material suitable for manufacturing thermistors for high temperature environments.
[0004] To achieve the above object, the present invention adopts the following technical solutions:
[0005] A double perovskite structure negative temperature coefficient thermistor material, the chemical general formula of the thermistor material is: A2ReNbO6, wherein A=Ba, Ca or Sr, Re=La, Nd or Sm, and the thermistor material is prepared by mixing and sintering raw materials of barium carbonate, calcium carbonate or strontium carbonate with lanthanum trioxide, neodymium trioxide or samarium trioxide and niobium pentoxide.
[0006] When A=Ca, the electrical properties of the thermistor material are B 400℃ / 1200℃=15480-17652K; when A=Sr, the electrical properties of the thermistor material are B 400℃ / 1000℃ =15356-20530K; when A=Ba, the electrical properties of the thermistor material are B 500℃ / 1200℃ =18750-21060K;
[0007] The double perovskite structure negative temperature coefficient thermistor material has an obvious negative temperature coefficient characteristic in the temperature range of 400°C-1200°C.
[0008] A method for preparing a double perovskite structure negative temperature coefficient thermistor material, the preparation method comprising the following steps:
[0009] a. According to the composition of A2ReNbO6, weigh niobium pentoxide, barium carbonate, calcium carbonate or strontium carbonate, lanthanum trioxide, neodymium trioxide or samarium trioxide, respectively, mix them together, ball mill, dry and grind them to obtain mixed powder;
[0010] b. calcining and grinding the mixed powder obtained in step a to obtain double perovskite structure A2ReNbO6 powder, wherein A=Ba, Ca or Sr, Re=La, Nd or Sm;
[0011] c. ball milling, drying and grinding the double perovskite structure A2ReNbO6 powder obtained in step b to obtain thermistor powder;
[0012] d. The thermistor powder obtained in step c is subjected to cold isostatic pressing and high-temperature sintering to obtain a double perovskite structured negative temperature coefficient thermistor material;
[0013] e. Coating platinum slurry electrodes on both sides of the double perovskite structure negative temperature coefficient thermistor material obtained in step d, and annealing at high temperature to obtain the double perovskite structure negative temperature coefficient thermistor material.
[0014] Preferably, in step a, analytically pure anhydrous ethanol is used as the dispersion medium, wet-milled for 15-25 hours, the wet-milled slurry is dried at a temperature of 75-85° C., taken out and milled for 0.5-3 hours to obtain a mixed powder.
[0015] Preferably, in step b, the calcination temperature is 950-1250° C., the calcination time is 5-7 hours, and the grinding time is 0.5-3 hours.
[0016] Preferably, in step c, analytically pure anhydrous ethanol is used as the dispersion medium, wet-milled for 7-9 hours, the wet-milled slurry is dried at a temperature of 75-85° C., taken out and milled for 0.5-3 hours to obtain thermistor powder.
[0017] Preferably, in step d, the powder is 10-20 kg / cm 2The block is pressed and formed at a pressure of 20-40s, and the formed block is cold isostatically pressed at a pressure of 200-300Mpa for 2-4min; the high-temperature sintering temperature is 1300-1500℃, and the sintering time is 4-12h.
[0018] Preferably, in step e, annealing is performed at 850-950° C. for 20-40 min.
[0019] According to a preferred embodiment of the present invention, the preparation of the double perovskite structure negative temperature coefficient thermistor material of the present invention is carried out according to the following steps:
[0020] a. According to the composition of A2ReNbO6, weigh niobium pentoxide and barium carbonate, calcium carbonate or strontium carbonate, lanthanum trioxide, neodymium trioxide or samarium trioxide respectively, put them into an agate ball mill, use analytical pure anhydrous ethanol as the dispersion medium, wet grind for 20 hours, dry the wet-milled slurry at 80°C, take it out and grind for 1 hour to obtain a mixed powder;
[0021] b. calcining the powder obtained in step a at a temperature of 950-1250° C. for 6 hours, and grinding for 1 hour to obtain double perovskite structure A2ReNbO6 (A=Ba, Ca, Sr; Re=La, Nd, Sm) powder;
[0022] c. Place the powder obtained in step b in an agate ball mill, use analytically pure anhydrous ethanol as a dispersion medium, wet-mill for 8 hours, dry the wet-milled slurry at 80° C., take it out and grind it for 1 hour to obtain thermistor powder;
[0023] d. The powder obtained in step c was heated to 15 kg / cm 2 The block is pressed and formed at a pressure of 300 MPa for 3 minutes, and then the block is sintered at a temperature of 1300-1500°C for 4-12 hours to obtain a double perovskite structure negative temperature coefficient thermistor material;
[0024] e. Coat the negative temperature coefficient thermistor material with a double perovskite structure obtained in step d with platinum slurry electrodes on both sides, and then anneal at 900° C. for 30 minutes.
[0025] Compared with the prior art, the advantages of the present invention are:
[0026] (1) The double perovskite structure A2ReNbO6 high temperature negative temperature coefficient thermistor material described in the present invention has typical NTC characteristics in a relatively high temperature range of 400°C-1200°C and has stable performance in a high temperature environment.
[0027] (2) The double perovskite structure A2ReNbO6 high temperature negative temperature coefficient thermistor material described in the present invention has a good linear relationship between lnρ and 1000 / T in a relatively high temperature range of 400°C-1200°C, and its linear fitting degree is above 0.999. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is a graph showing the relationship between the resistivity and temperature of the Ba2ReNbO6 (Re=La, Nd, Sm) material of the present invention;
[0029] Figure 2 is a graph showing the relationship between the resistivity and temperature of the Ca2ReNbO6 (Re=La, Nd, Sm) material of the present invention;
[0030] Figure 3 Graph showing the relationship between resistivity and temperature of the Sr2ReNbO6 (Re=La, Nd, Sm) material of the present invention. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is described in detail below with reference to the accompanying drawings and embodiments.
[0032] Example 1
[0033] A method for preparing a double perovskite structure negative temperature coefficient thermistor material, the preparation method comprising the following steps:
[0034] a. According to the composition of Ba2LaNbO6, weigh barium carbonate, lanthanum trioxide and niobium pentoxide, mix them, put them in an agate ball mill, use anhydrous ethanol as the dispersion medium, wet grind for 15 hours, dry the wet-milled slurry at 75°C, take it out and grind it for 0.5 hours to obtain powder;
[0035] b. calcining the powder in step a at 1250° C. for 5 h, and grinding for 0.5 h to obtain a powder;
[0036] c. Place the powder obtained in step b in an agate ball mill, use analytically pure anhydrous ethanol as a dispersion medium, wet-mill for 7 hours, dry the wet-milled slurry at 75° C., take it out and grind it for 0.5 hours to obtain thermistor powder;
[0037] d. The powder obtained in step c was heated to 10 kg / cm 2 The block is pressed and formed at a pressure of 200 MPa for 4 min, and then the block is sintered at 1450°C for 4 h to obtain a double perovskite structured negative temperature coefficient thermistor material.
[0038] e. Coat the positive and negative sides of the double perovskite structured negative temperature coefficient thermistor material obtained in step d with platinum paste electrodes, and then anneal at 850°C for 40 minutes to obtain the electrical performance parameters: B 500℃ / 1200℃ =20530K,ρ 1200℃ =2.54×10 3 Ω·cm barium lanthanum niobate negative temperature coefficient thermistor material.
[0039] The relationship between the resistivity and temperature of the barium lanthanum niobate negative temperature coefficient thermistor material is shown in the figure below: Figure 1 shown.
[0040] Example 2
[0041] A method for preparing a double perovskite structure negative temperature coefficient thermistor material, the preparation method comprising the following steps:
[0042] a. According to the composition of Ba2NdNbO6, weigh barium carbonate, neodymium trioxide and niobium pentoxide, mix them, put them in an agate ball mill, use anhydrous ethanol as the dispersion medium, wet grind for 20 hours, dry the wet-milled slurry at 80°C, take it out and grind it for 1 hour to obtain powder;
[0043] b. calcining the powder in step a at 1250° C. for 6 h, and grinding for 1 h to obtain a powder;
[0044] c. Place the powder obtained in step b in an agate ball mill, use analytically pure anhydrous ethanol as a dispersion medium, wet-mill for 8 hours, dry the wet-milled slurry at 80° C., take it out and grind it for 1 hour to obtain thermistor powder;
[0045] d. The powder obtained in step c was heated to 15 kg / cm 2 The block is pressed and formed at a pressure of 300 MPa for 30 seconds, and the formed block is cold isostatically pressed at a pressure of 300 MPa for 3 minutes, and then the block is sintered at a temperature of 1475°C for 4 hours to obtain a double perovskite structure negative temperature coefficient thermistor material;
[0046] e. Coat the positive and negative temperature coefficient thermistor material of the double perovskite structure obtained in step d with platinum slurry electrodes on both sides, and then anneal at 900°C for 30 minutes to obtain the electrical performance parameters: B 500℃ / 1200℃ =18750K,ρ 1200℃ =2.82×10 3 Ω·cm barium neodymium niobate negative temperature coefficient thermistor material.
[0047] The relationship between the resistivity and temperature of the barium neodymium niobate negative temperature coefficient thermistor material is shown in the figure below: Figure 1 shown.
[0048] Example 3
[0049] A method for preparing a double perovskite structure negative temperature coefficient thermistor material, the preparation method comprising the following steps:
[0050] a. According to the composition of Ba2SmNbO6, weigh barium carbonate, samarium trioxide and niobium pentoxide, mix them, put them in an agate ball mill, use anhydrous ethanol as the dispersion medium, wet grind for 25 hours, dry the wet-milled slurry at 85°C, take it out and grind for 2 hours to obtain powder;
[0051] b. calcining the powder in step a at 1250° C. for 7 h, and grinding for 2 h to obtain a powder;
[0052] c. Place the powder obtained in step b in an agate ball mill, use analytically pure anhydrous ethanol as a dispersion medium, wet-mill for 9 hours, dry the wet-milled slurry at 85° C., take it out and grind it for 3 hours to obtain thermistor powder;
[0053] d. The powder obtained in step c was heated to 20 kg / cm 2 The block is pressed and formed at a pressure of 300 MPa for 2 min, and then the block is sintered at 1500°C for 12 h to obtain a double perovskite structured negative temperature coefficient thermistor material.
[0054] e. Coat the positive and negative sides of the double perovskite structured negative temperature coefficient thermistor material obtained in step d with platinum slurry electrodes, and then anneal at 950°C for 20 minutes to obtain the electrical performance parameters: B 500℃ / 1200℃ =21060K,ρ 1200℃ =3.47×10 3 Ω·cm barium samarium niobate negative temperature coefficient thermistor material.
[0055] The relationship between the resistivity and temperature of the barium samarium niobate negative temperature coefficient thermistor material is shown in the figure below: Figure 1 shown.
[0056] Example 4
[0057] A method for preparing a double perovskite structure negative temperature coefficient thermistor material, the preparation method comprising the following steps:
[0058] a. According to the composition of Ca2LaNbO6, calcium carbonate, lanthanum trioxide and niobium pentoxide are weighed and mixed, placed in an agate ball mill, and wet-milled for 15 hours with anhydrous ethanol as the dispersion medium. The wet-milled slurry is dried at 75°C, taken out and milled for 1 hour to obtain a powder;
[0059] b. calcining the powder in step a at 950° C. for 6 h, and grinding for 1 h to obtain a powder;
[0060] c. Place the powder obtained in step b in an agate ball mill, use analytically pure anhydrous ethanol as a dispersion medium, wet-mill for 7 hours, dry the wet-milled slurry at 75° C., take it out and grind it for 1 hour to obtain thermistor powder;
[0061] d. The powder obtained in step c was heated to 10 kg / cm 2 The block is pressed and formed at a pressure of 200 MPa for 40 seconds, and the formed block is cold isostatically pressed at a pressure of 200 MPa for 4 minutes, and then the block is sintered at a temperature of 1300°C for 8 hours to obtain a double perovskite structure negative temperature coefficient thermistor material;
[0062] e. Coat the positive and negative sides of the double perovskite structured negative temperature coefficient thermistor material obtained in step d with platinum paste electrodes, and then anneal at 850°C for 40 minutes to obtain the electrical performance parameters: B 400℃ / 1200℃ =16444K,ρ 1200℃ =5.18×10 3 Ω·cm calcium lanthanum niobate negative temperature coefficient thermistor material.
[0063] The relationship between the resistivity and temperature of calcium lanthanum niobate negative temperature coefficient thermistor material is shown in the figure below: Figure 2 shown.
[0064] Example 5
[0065] A method for preparing a double perovskite structure negative temperature coefficient thermistor material, the preparation method comprising the following steps:
[0066] a. According to the composition of Ca2NdNbO6, calcium carbonate, neodymium trioxide and niobium pentoxide are weighed and mixed, placed in an agate ball mill, and wet-milled for 20 hours with anhydrous ethanol as the dispersion medium. The wet-milled slurry is dried at 80°C, taken out and milled for 1 hour to obtain a powder;
[0067] b. calcining the powder in step a at 950° C. for 6 h, and grinding for 1 h to obtain a powder;
[0068] c. Place the powder obtained in step b in an agate ball mill, use analytically pure anhydrous ethanol as a dispersion medium, wet-mill for 8 hours, dry the wet-milled slurry at 80° C., take it out and grind it for 1 hour to obtain thermistor powder;
[0069] d. The powder obtained in step c was heated to 15 kg / cm 2 The block is pressed and formed at a pressure of 300 MPa for 30 seconds, and the formed block is cold isostatically pressed at a pressure of 300 MPa for 3 minutes, and then the block is sintered at a temperature of 1300°C for 8 hours to obtain a double perovskite structure negative temperature coefficient thermistor material;
[0070] e. Coat the positive and negative temperature coefficient thermistor material of the double perovskite structure obtained in step d with platinum slurry electrodes on both sides, and then anneal at 900°C for 30 minutes to obtain the electrical performance parameters: B 400℃ / 1200℃ =15480K,ρ 1200℃ =4.47×10 3 Ω·cm calcium neodymium niobate negative temperature coefficient thermistor material.
[0071] The relationship between the resistivity and temperature of the calcium niobate neodymium negative temperature coefficient thermistor material is shown in the figure below: Figure 2 shown.
[0072] Example 6
[0073] A method for preparing a double perovskite structure negative temperature coefficient thermistor material, the preparation method comprising the following steps:
[0074] a. According to the composition of Ca2SmNbO6, calcium carbonate, samarium trioxide and niobium pentoxide are weighed and mixed, placed in an agate ball mill, and wet-milled for 25 hours with anhydrous ethanol as the dispersion medium. The wet-milled slurry is dried at 85°C, taken out and milled for 2 hours to obtain a powder;
[0075] b. calcining the powder in step a at 950° C. for 7 h, and grinding for 2 h to obtain a powder;
[0076] c. Place the powder obtained in step b in an agate ball mill, use analytically pure anhydrous ethanol as a dispersion medium, wet-mill for 9 hours, dry the wet-milled slurry at 85° C., take it out and grind it for 3 hours to obtain thermistor powder;
[0077] d. The powder obtained in step c was heated to 20 kg / cm 2 The block is pressed and formed at a pressure of 200 MPa for 40 seconds, and the formed block is cold isostatically pressed at a pressure of 200 MPa for 4 minutes, and then the block is sintered at a temperature of 1300°C for 8 hours to obtain a double perovskite structure negative temperature coefficient thermistor material;
[0078] e. Coat the positive and negative sides of the double perovskite structured negative temperature coefficient thermistor material obtained in step d with platinum slurry electrodes, and then anneal at 950°C for 20 minutes to obtain the electrical performance parameters: B 400℃ / 1200℃ =17652K,ρ 1200℃ =4.41×10 3 Ω·cm calcium samarium niobate negative temperature coefficient thermistor material.
[0079] The relationship between the resistivity and temperature of the calcium samarium niobate negative temperature coefficient thermistor material is shown in the figure below: Figure 2 shown.
[0080] Example 7
[0081] A method for preparing a double perovskite structure negative temperature coefficient thermistor material, the preparation method comprising the following steps:
[0082] a. According to the composition of Sr2LaNbO6, weigh strontium carbonate, lanthanum trioxide and niobium pentoxide, mix them, put them in an agate ball mill, use anhydrous ethanol as the dispersion medium, wet grind for 15 hours, dry the wet-milled slurry at 75°C, take it out and grind it for 1 hour to obtain powder;
[0083] b. calcining the powder in step a at 950° C. for 6 h, and grinding for 1 h to obtain a powder;
[0084] c. Place the powder obtained in step b in an agate ball mill, use analytically pure anhydrous ethanol as a dispersion medium, wet-mill for 7 hours, dry the wet-milled slurry at 75° C., take it out and grind it for 1 hour to obtain thermistor powder;
[0085] d. The powder obtained in step c was heated to 10 kg / cm 2 The block is pressed and formed at a pressure of 200 MPa for 40 seconds, and the formed block is cold isostatically pressed at a pressure of 200 MPa for 4 minutes, and then the block is sintered at a temperature of 1300°C for 8 hours to obtain a double perovskite structure negative temperature coefficient thermistor material;
[0086] e. Coat the positive and negative sides of the double perovskite structured negative temperature coefficient thermistor material obtained in step d with platinum paste electrodes, and then anneal at 850°C for 40 minutes to obtain the electrical performance parameters: B 400℃ / 1000℃ =15356K,ρ 1000℃ =1.23×10 3 Ω·cm Strontium lanthanum niobate negative temperature coefficient thermistor material.
[0087] The relationship between the resistivity and temperature of strontium lanthanum niobate negative temperature coefficient thermistor material is shown in the figure Figure 3 shown.
[0088] Example 8
[0089] A method for preparing a double perovskite structure negative temperature coefficient thermistor material, the preparation method comprising the following steps:
[0090] a. According to the composition of Sr2NdNbO6, weigh strontium carbonate, neodymium trioxide and niobium pentoxide, mix them, put them in an agate ball mill, use anhydrous ethanol as a dispersion medium, wet grind for 20 hours, dry the wet-milled slurry at 80°C, take it out and grind it for 1 hour to obtain powder;
[0091] b. calcining the powder in step a at 950° C. for 6 h, and grinding for 1 h to obtain a powder;
[0092] c. Place the powder obtained in step b in an agate ball mill, use analytically pure anhydrous ethanol as a dispersion medium, wet-mill for 8 hours, dry the wet-milled slurry at 80° C., take it out and grind it for 1 hour to obtain thermistor powder;
[0093] d. The powder obtained in step c was heated to 15 kg / cm 2 The block is pressed and formed at a pressure of 300 MPa for 30 seconds, and the formed block is cold isostatically pressed at a pressure of 300 MPa for 3 minutes, and then the block is sintered at a temperature of 1300°C for 8 hours to obtain a double perovskite structure negative temperature coefficient thermistor material;
[0094] e. Coat the positive and negative temperature coefficient thermistor material of the double perovskite structure obtained in step d with platinum slurry electrodes on both sides, and then anneal at 900°C for 30 minutes to obtain the electrical performance parameters: B 400℃ / 1000℃ =15514K,ρ 1000℃ =1.21×10 3 Strontium neodymium niobate negative temperature coefficient thermistor material with a resistance of Ω·cm.
[0095] The relationship between the resistivity and temperature of the SrNdNdNd negative temperature coefficient thermistor material is shown in the figure below: Figure 3 shown. Figure 3 In the figure, the relationship line between the resistivity and temperature of the strontium-neodymium niobate negative temperature coefficient thermistor material and the relationship line between the resistivity and temperature of the strontium-lanthanum niobate negative temperature coefficient thermistor material are overlapped.
[0096] Example 9
[0097] A method for preparing a double perovskite structure negative temperature coefficient thermistor material, the preparation method comprising the following steps:
[0098] a. According to the composition of Sr2SmNbO6, weigh strontium carbonate, samarium trioxide and niobium pentoxide, mix them, put them in an agate ball mill, use anhydrous ethanol as the dispersion medium, wet grind for 25 hours, dry the wet-milled slurry at 85°C, take it out and grind for 2 hours to obtain powder;
[0099] b. calcining the powder in step a at 950° C. for 7 h, and grinding for 2 h to obtain a powder;
[0100] c. Place the powder obtained in step b in an agate ball mill, use analytically pure anhydrous ethanol as a dispersion medium, wet-mill for 9 hours, dry the wet-milled slurry at 85° C., take it out and grind it for 3 hours to obtain thermistor powder;
[0101] d. The powder obtained in step c was heated to 20 kg / cm 2 The block is pressed and formed at a pressure of 300 MPa for 2 min, and then the block is sintered at a temperature of 1325°C for 8 h to obtain a double perovskite structured negative temperature coefficient thermistor material.
[0102] e. Coat the positive and negative sides of the double perovskite structured negative temperature coefficient thermistor material obtained in step d with platinum slurry electrodes, and then anneal at 950°C for 20 minutes to obtain the electrical performance parameters: B 500℃ / 1000℃ =20530K,ρ 1000℃ =21.51×10 3 Ω·cm strontium samarium niobate negative temperature coefficient thermistor material.
[0103] The relationship between the resistivity and temperature of the SrNbO3 negative temperature coefficient thermistor material is shown in the figure below: Figure 3 shown.
[0104] Figure 1-Figure 3 It is shown that the double perovskite structure high temperature negative temperature coefficient thermistor material described in the present invention has a good linear relationship between lnρ and 1000 / T in a relatively high temperature range of 400°C-1200°C, and the linear fitting degree is above 0.999.
[0105] The process parameters (such as temperature, time, etc.) of the present invention can realize the method by taking upper and lower limits and interval values, and the embodiments are not listed one by one here.
[0106] Any contents not described in detail in the present invention can be based on the conventional technical knowledge in the art.
[0107] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the embodiments, it should be understood by those skilled in the art that any modification or equivalent replacement of the technical solutions of the present invention does not depart from the spirit and scope of the technical solutions of the present invention and should be included in the scope of the claims of the present invention.
Claims
1. A double perovskite structure negative temperature coefficient thermistor material, characterized in that: The general chemical formula of the thermistor material is: A2ReNbO6, wherein A=Ba, Ca or Sr, Re=La, Nd or Sm, and the thermistor material is prepared by mixing and sintering raw materials of barium carbonate, calcium carbonate or strontium carbonate with lanthanum trioxide, neodymium trioxide or samarium trioxide and niobium pentoxide.
2. The double perovskite structure negative temperature coefficient thermistor material according to claim 1, characterized in that: When A = Ca, the electrical properties of the thermistor material are B 400℃ / 1200℃ =15480-17652K; when A=Sr, the electrical properties of the thermistor material are B 400℃ / 1000℃ =15356-20530K; when A=Ba, the electrical properties of the thermistor material are B 500℃ / 1200℃ =18750-21060K; The double perovskite structure negative temperature coefficient thermistor material has an obvious negative temperature coefficient characteristic in the temperature range of 400°C-1200°C.
3. A method for preparing a double perovskite structure negative temperature coefficient thermistor material, the preparation method comprising the following steps: a. According to the composition of A2ReNbO6, weigh niobium pentoxide, barium carbonate, calcium carbonate or strontium carbonate, lanthanum trioxide, neodymium trioxide or samarium trioxide, respectively, and mix them together, ball mill, dry and grind them to obtain mixed powder; b. calcining and grinding the mixed powder obtained in step a to obtain double perovskite structure A2ReNbO6 powder, wherein A=Ba, Ca or Sr, Re=La, Nd or Sm; c. ball milling, drying and grinding the double perovskite structure A2ReNbO6 powder obtained in step b to obtain thermistor powder; d. The thermistor powder obtained in step c is subjected to cold isostatic pressing and high-temperature sintering to obtain a double perovskite structured negative temperature coefficient thermistor material; e. Coating platinum slurry electrodes on both sides of the double perovskite structure negative temperature coefficient thermistor material obtained in step d, and annealing at high temperature to obtain the double perovskite structure negative temperature coefficient thermistor material.
4. The preparation method according to claim 3, characterized in that: In step a, analytically pure anhydrous ethanol is used as a dispersion medium, wet-milled for 15-25 hours, the wet-milled slurry is dried at a temperature of 75-85° C., taken out and milled for 0.5-3 hours to obtain a mixed powder.
5. The preparation method according to claim 3, characterized in that: In step b, the calcination temperature is 950-1250° C., the calcination time is 5-7 hours, and the grinding time is 0.5-3 hours.
6. The preparation method according to claim 3, characterized in that: In step c, analytically pure anhydrous ethanol is used as a dispersion medium, wet-milled for 7-9 hours, the wet-milled slurry is dried at a temperature of 75-85° C., taken out and milled for 0.5-3 hours to obtain thermistor powder.
7. The preparation method according to claim 3, characterized in that: In step d, the powder is 10-20kg / cm 2 The block is pressed and formed at a pressure of 20-40s, and the formed block is cold isostatically pressed at a pressure of 200-300Mpa for 2-4min; the high-temperature sintering temperature is 1300-1500℃, and the sintering time is 4-12h.
8. The preparation method according to claim 3, characterized in that: In step e, annealing is performed at 850-950° C. for 20-40 min.
Citation Information
Patent Citations
Resistive element, infrared light sensor, and electrical device
CN102597724A
Preparation method of Ba2SmNbO6 microwave dielectric material
CN110590335A
Preparation method of Sr2SmNbO6 microwave dielectric material
CN110606741A
Preparation method of double perovskite type and yttrium oxide compounded negative temperature coefficient thermistor material
CN113979728A
Deep red fluorescent substance, light source for use in illumination, and method for manufacturing deep red fluorescent substance
JP2013001877A